Knowledge hiding behavior in higher education institutions: a scientometric analysis and systematic literature review approach - Fauzi, Muhammad Ashraf (Journal of Knowledge Management, 2022)
Purpose The purpose of this paper is to systematically review knowledge hiding (KH) behavior in higher education institutions (HEIs). KH is regarded as an unethical and antisocial behavior by many scholars, which should not be prevalent in HEIs. Design/methodology/approach A two-phase analysis through quantitative scientometric analysis and qualitative systematic literature review method through the preferred reporting items for systematic reviews and meta-analyses (PRISMA) model was applied. In phase 1,174 articles were analyzed using the VOSviewer through co-word and co-citation analyses. In Phase 2, 20 related studies on KH in HEIs were qualitatively analyzed on the fundamental concept of KH. The main themes were determined based on current research findings, through the identification of relevant gaps in the context of higher education. Findings In Phase 1, co-word and co-citation analyses resulted in six and three clusters, respectively. Subsequently, in Phase 2, five themes were discovered: terminology of KH, scale of KH, cultural and geographical context, KH among academics and students and relevant theories. Further, discussion on the institutional factors of individuals, organizations, technology and culture is presented. Practical implications This review lays out a practical guide to facilitate HEIs in managing KH behavior among academics, employees, and students. Strategies can be planned and implemented to foster and inculcate knowledge sharing behavior to circulate knowledge while at the same time diminishing KH behavior in HEIs. Originality/value To the best of the author’s knowledge, this study is the first to review KH behavior in the context of HEIs through quantitative and qualitative analysis.
Keywords: Academics; Higher education institution; Knowledge hiding; Knowledge sharing; Students